A Modern Approach to Teaching Econometrics (European Journal of Pure and Applied Mathematics, 2010)
We explain the computer-based approach to the teaching of econometrics used in Oxford from the elementary to the advanced. The aims are to enable students to critically evaluate published applied studies and to undertake empirical research in economics. The unified theoretical framework is that of likelihood, using likelihood-ratio tests for inference and evaluation, and focusing on developing well-specified empirical models of interesting economic issues. A sequence of increasingly realistic models is developed from independent, identically distributed binary data through to selecting cointegrated equations in the face of structural breaks–in a one-year course.